2015
DOI: 10.1111/ced.12702
|View full text |Cite
|
Sign up to set email alerts
|

Familial progressive hyper- and hypopigmentation and malignancy in two families with new mutations inKITLG

Abstract: We summarize the genetic spectrum of the dyschromatoses and discuss a possible increased risk of malignancy in FPHH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 9 publications
2
21
0
Order By: Relevance
“…3 Two heterozygous missense mutations were found in two unrelated Caucasian families with FPHH. 15 This study confirmed that the gene underlying FPHH is the KITLG gene, which has also been demonstrated in separate studies. 4,5 …”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…3 Two heterozygous missense mutations were found in two unrelated Caucasian families with FPHH. 15 This study confirmed that the gene underlying FPHH is the KITLG gene, which has also been demonstrated in separate studies. 4,5 …”
Section: Discussionsupporting
confidence: 87%
“…14 Two unrelated Caucasian families had six members affected with FPHH who had unusually sparse lateral eyebrows, two of whom had cancer. 15 …”
Section: Discussionmentioning
confidence: 99%
“…KITLG mutation is a rare cause of WS, with only one case having been reported (Zazo Seco et al, 2015). KITLG is also associated with another pigmentary disorder: familial progressive hyper-and hypopigmentation (FPHH, OMIM #145250; Amyere et al, 2011;Cuell et al, 2015;Wang et al, 2009). Here, we report the second case of WS2 caused by a KITLG mutation with a rare manifestation of pigmented macules.…”
mentioning
confidence: 90%
“…To our knowledge, until now only five different missense KITLG mutations (Val33Ala, Thr34Pro, Thr34Asn, Asn36Ser and Val37Gly) have been reported to cause FPHH . Notably, Asn36Ser was also shown to be responsible for a distinct phenotype called FPH .…”
mentioning
confidence: 99%